Study of the Couple Stress Convective Micropolar Fluid Flow in a Hall MHD Generator System - Shah, Zahir; Kumam, Poom; Dawar, Abdullah; Alzahrani, Ebraheem O.; Thounthong, Phatiphat (Frontiers in Physics, 2019)
The steady non-isothermal convective heat transfer in magnetohydrodynamic micropolar fluid flow over a non-linear extending wall is examined. The fluid flow is treated with strong magnetic field. The influence of magnetic field, Hall current, and couple stress are mainly focused in this work. The fluid flow problem is solved analytically. The impact of developing dimensionless parameters on primary, secondary, and angular velocity components and temperature profile are determined through graphs. The primary velocity component has reduced throughout the flow study. The greater magnetic parameter, Hall parameter and couple stress parameter have increased the secondary velocity component while the local Grashof number has reduced the secondary velocity component. The greater magnetic parameter and Hall parameter have reduced the angular velocity component. The greater magnetic parameter has increased the temperature profile while the Hall parameter and local Grashof number have decreased the temperature profile. The impact of developing dimensionless parameters on skin friction coefficient and local Nusselt number are determined through Tables.